Viral hepatitis - Thomas, H. C; Lemon, Stanley M; Zuckerman, Arie J (Blackwell Publishing, 2005)
There has been an explosion of both the incidence and medical knowledge of viral hepatitis over the last two decades. Not only is the incidence of infection and disease increasing, but new hepatitis viruses have been discovered, as well as the launch of new pharmaceutical products.Previously published by Churchill Livingstone, Viral Hepatitis by Zuckerman & Thomas was the first comprehensive book on hepatitis and is recognized as the standard reference text in this field. The new third edition, now published by Blackwell Publishing, addresses the recent advances in diagnosis and treatment with entirely revised and current topics. It covers the entire spectrum of viral hepatitis and has something of interest for every specialist. Viral Hepatitis presents the latest thinking from the leading international researchers and clinicians working in this field and the Editors are joined by a North American co-Editor for this edition - Professor Stanley Lemon of the University of Texas, Galveston, TX, USA. This book offers an ideal reference for all healthcare professionals involved in the research and patient care of this disease.
Keywords: Hepatitis Viruses; nemoci jater; viry hepatitidy; Liver Diseases; gastroenterologie; infekční lékařství; Hepatitis, Viral, Human; virová hepatitida u lidí